2023
DOI: 10.3390/foods12163022
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Dietary Exposure to Acrylamide from Foods Consumed within and outside Main Meals in Singapore

Abstract: This study investigated the influence of ‘snackification’ in Singaporean diets, leading to increased dietary acrylamide exposure. Acrylamide concentrations in commonly consumed foods within and outside the main meals were measured using liquid chromatography with tandem mass spectrometry (LC-MS/MS). High acrylamide concentrations were detected in vegetables cooked at high temperatures (ranging from 0.5 to 478.4 µg/kg) and potato-based crackers and chips (ranging from 81.8 to 2095.8 µg/kg). The estimated total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The levels of 3-MCPD esters and glycidyl esters in this study were the highest in fats and oils (731 ppb) and RTE savouries (538 ppb). A detailed discussion on acrylamide, 3-MCPD esters and glycidyl esters tested in foods from this study has previously been published [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of 3-MCPD esters and glycidyl esters in this study were the highest in fats and oils (731 ppb) and RTE savouries (538 ppb). A detailed discussion on acrylamide, 3-MCPD esters and glycidyl esters tested in foods from this study has previously been published [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The mean concentrations for metals and processed contaminants studied in Singapore's TDS by food category are shown in Tables 4 and 5. Concentration data for the other chemical groups can be found in Tables S12 to S15 of Supplementary Information, and elsewhere [38][39][40].…”
Section: Chemical Concentrations Found In Foodsmentioning
confidence: 99%
“…In this study, a deterministic method was used to estimate the dietary exposure to 3-MCPDEs and GEs of an individual consumer (µg/kg bw/day) (Equation ( 1)) [37]:…”
Section: Dietary Exposure Assessmentmentioning
confidence: 99%
“…The literature has shown that the quality of food is closely linked to both primary and secondary food production processes [49]. Cooking methods used for home cooking can not only significantly impact the natural phytochemical compositions and biological characteristics of the food, but also introduce processed contaminants to the food [37,50,51]. Our study investigated the occurrence of 3-MCPDEs and GEs in domestically cooked food prepared with different cooking methods.…”
Section: Occurrence Of 3-mcpdes and Ges In Domestically Prepared Foodmentioning
confidence: 99%